Improving Student’s Vocabulary By Picture Card for Enhancing Student’s Interest In Learning English at SMP Tahfidz Al Azhar Ledokombo - Nayli Nuril Fadlullah; Qoniatul Mubarokah; Fadillah Wulansari (Jurnal Studi Guru dan Pembelajaran, 2026)
This study aimed to improve seventh-grade students’ vocabulary mastery and learning interest in English through the use of picture cards at SMP Tahfidz Al Azhar Ledokombo. The study was based on preliminary observation showing that students had limited vocabulary mastery, difficulty remembering and using new words, low motivation, and limited classroom participation. This research employed Classroom Action Research (CAR) with qualitative and quantitative descriptive approaches. The participants were 15 seventh-grade students, consisting of 7 male and 8 female students. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through vocabulary tests, classroom observation sheets, and field notes. The results showed that students’ learning completeness increased from 4 out of 15 students in the pre-cycle stage to 14 out of 15 students in Cycle II. Observation results also indicated better learning interest, shown through increased enthusiasm, attention, participation, and vocabulary recall. Therefore, picture cards can be used as an alternative teaching medium to support vocabulary learning and classroom engagement in junior high school English instruction.